Enzymatic characterization of insecticide resistance mechanisms in field populations of Malaysian culex quinquefasciatus Say (Diptera: Culicidae) - Low, Van Lun; Chen, Chee Dhang; Lee, Han Lim; Tan, Tiong Kai; Chen, Chin Fong; Leong, Cherng Shii; Lim, Yvonne Ai Lian; Lim, Phaik Eem; Norma-Rashid, Yusoff; Sofian-Azirun, Mohd (Public Library of Science, 2013)
Background: There has been no comprehensive study on biochemical characterization of insecticide resistance mechanisms in field populations of Malaysian Culex quinquefasciatus. To fill this void in the literature, a nationwide investigation was performed to quantify the enzyme activities, thereby attempting to characterize the potential resistance mechanisms in Cx. quinquefasciatus in residential areas in Malaysia. Methodology/Principal Findings: Culex quinquefasciatus from 14 residential areas across 13 states and one federal territory were subjected to esterases, mixed function oxidases, glutathione-S-transferase and insensitive acetylcholinesterase assays. Enzyme assays revealed that alpha-esterases and beta-esterases were elevated in 13 populations and 12 populations, respectively. Nine populations demonstrated elevated levels of mixed function oxidases and glutathione-S-transferase. Acetylcholinesterase was insensitive to propoxur in all 14 populations. Activity of alpha-esterases associated with malathion resistance was found in the present study. In addition, an association between the activity of alpha-esterases and beta-esterases was also demonstrated. Conclusions/Significance: The present study has characterized the potential biochemical mechanisms in contributing towards insecticide resistance in Cx. quinquefasciatus field populations in Malaysia. Identification of mechanisms underlying the insecticide resistance will be beneficial in developing effective mosquito control programs in Malaysia.